Perbandingan Keberlanjutan Bisnis Retail Minimarket Modern dan Retail Tradisional Warung di Jawa Barat - Efrita Norman; Yudi Permana; Riris Aishah Prasetyowati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
The Continuity of traditional and modern retail retail business attracts the most attention, because it always puts the traditional retail business in a weak position. The result of this research is that the attention to the successful aspects of the service industry has not been a concern for the traditional retail business, thus weakening the position of traditional Retail business, coupled with the strong characteristic of the standardized service quality dimension as the business reference of modern minimarket services increasingly sharpening the performance gap retail business and thus further weaken the position of traditional retail business. Comparative analysis of Retail Business Traditional Stores and Retail Business Modern minimarket shows the successful aspects of the service business to be considered namely; consumers, management, and employees. This research includes descriptive research type using traditional approach. The analysis method used is a variant of semantic differential approach, with descriptive statistic analysis, correlation analysis, regression analysis to obtain determinant of the purpose of this research.